PERBEDAAN SIFAT KARAKTERISTIK FISIK GRANUL EFFERVESCENT EKSTRAK KUNYIT (Curcuma damestica Val.) ASAM (Tamarindus Indica L.) DENGAN BAHANPENGISI DEKSTROSA, SUKROSA, DEKSTROSA-SUKROSA (50 : 50) - Siti Munisih; Hani Citra Hartati; M. Amroni (Media Farmasi Indonesia, 2010)
ABSTRACT Many kinds of technology have already been used to develop kunyit asam preparation, in a form of granul effervescent. The aim of this research is to know how the physical characteristic of granul effervescent from kunyit asam with different fillers such as dekstrosa, sakarose and dextrose-sakarose (50 : 50). Tests of physical characteristic of granul effervescent from kunyit asam included moisture content, flow time, angle of repose, solubility time, bulk volume, tapping and it was added by additional tests that were ALT and the sensory of flavour. Based on this research, the result of formula I had moisture content 2.84 %, flow time 8.25 seconds, angle of repose 32.61°, solubility time 1.45 minutes,bulk volume 42.165 g/100 ml, tapping 9,50%, the ALT bacteria was 1.7x101CFU/ml, chamir 3.3x101 CFU/ml and it was not too sweet, quite salty, quite acid, not bitter. Formula II had moisture content 3.54%, flow time 6.38 seconds, angle of repose 26.15°, solubility time 1.29 minutes, bulk volume 47.190 g/100 ml, tapping 6.30%, the ALT bacteria was 1.9x101 CFU/ml, kapang 3.8x101 CFU/ml and have quite sweet, quite salty, not too acid, not bitter taste. Formula III (detrosa- sakarose (50 : 50)) moisture content 3.26%, flow time 7.24 seconds, angle of repose 29.09°, solubility time 1.13 minutes, bulk volume 45.812 g/100 ml, tapping 7.80%, the ALT bacteria was 1.3x101CFU/ml, kapang 3.4x101CFU /ml and it was quite sweet, no too salty, quite acid, not bitter . The result from Kruskal-Wallis and Mann-Whitney test, Anova and Pasca Anava test showed that there was no significant difference of moisture content, flow time, angle of repose and solubility time between the formulas.